Pengaruh Agama Dalam Pembentukan Tanggung Jawab, Moral, Dan Etika Sosial Masyarakat - Noorizki, Adisaputra Zidha; Fauziyah, Ananda; Aktafarid, Ardhana Wahyu (Program Studi Pendidikan Agama Islam, 2022)
“The Global God Divide” survey conducted by the Pew Research Center in 2020 revealed that Indonesia has the highest ranking as a highly religious country. As many as 98% of respondents stated that religion plays an important role in their lives. In the face of the complexity of modern-day challenges, a deep understanding of how religion influences individual views and behaviors is crucial. This research adopts the literature study method to analyze existing scholarly writings, focusing on the role of religion and its impact on the formation of people's social responsibility, morals, and ethics. Faith-based character education can be a powerful tool in shaping individual character and fostering social responsibility. The integration of religious values in education through programs such as religious ethics discussions, interactive understanding tools, religious values competitions, and religious values-based community projects can help in understanding and internalizing moral principles in life.